Limb length discrepancy after total hip arthroplasty: a systematic review - Pathak, Pradeep Kumar; Gupta, Rakesh Kumar; Meena, Hari Singh; Fiske, Rajendra (International Journal of Research in Orthopaedics, 2018)
Correcting limb length inequality without compromising hip stability is one of the major intraoperative challenges in Total hip arthroplasty (THA) as it is a major cause of patient dissatisfaction and litigation against surgeon. Surgeons performing THA should aim to minimize Limb Length Discrepancy (LLD), and therefore should adopt a reliable method of doing so. Thus a reproducible technique which effectively reduces postoperative LLD without increasing operative time and is easy to apply is a need of time. Although various preoperative and intraoperative techniques are described in literature, none is universally applicable and is without limitations. We are presenting a review of 50 articles on limb length discrepancy after total hip arthroplasty, its implications and several techniques to avoid it. We suggest that every effort should be made to minimise postoperative Limb Length Discrepancy by combined use of preoperative and intraoperative techniques.